The Influence of Islamic-Based Learning on Character Formation of Students at MTs Nurul Islam Radungkal - Desti Rahmawati (Journal of Islamic Religious Studies, 2024)
This study examines the impact of Islamic-based learning on the character development of students at MTs Nurul Islam Radungkal. The research aimed to evaluate how integrating Islamic values into education influences the moral and social growth of students. A quantitative research design with a one-group pretest-posttest model was used, focusing on Grade IX A students, totaling 42 participants. Data were collected through pre- and post-test questionnaires, observations, interviews, and academic records. The results demonstrated significant improvements in the students' character traits, such as honesty, discipline, responsibility, and empathy. The post-test scores increased notably from 65.3 to 81.2. Statistical analysis confirmed that the intervention had a substantial impact on character development, with a p-value of less than 0.001, indicating a significant effect. These findings suggest that Islamic-based learning plays a crucial role in enhancing students' moral values, offering a valuable approach for educational institutions aiming to incorporate Islamic teachings into their curricula. The study highlights the potential of this method to foster stronger ethical foundations in students and encourages further research into the broader implications of character-based educational strategies. By integrating Islamic principles, schools can contribute to the holistic development of students, preparing them for socially responsible and morally grounded lives. This research provides evidence that Islamic-based learning can effectively support the cultivation of essential values within educational settings.